Intérprete e eletrônica: análise de Poucas Linhas de Ana Cristina de Silvio Ferraz para clarineta solo e com eletrônica ao vivo - Flavio Ferreira da Silva (2007)
Throughout 20th century the development of electronic and digital musical technologies influenced listening, composition and performance. The advent of sound recording at the end of 19th century disconnected musical hearing of its visual aspects and more attention was given to sound. Changes in the way of music listening lead to different compositional approaches such as electroacoustic music. Putting together electroacoustics equipments with live performance of traditional music instruments brought new challenges to the performer such as interaction with loudspeakers and time inflexible pre-recorded musical parts and the manipulation of interfaces to control live electronic. The purpose of this work is to discuss the questions that confront the performer when he plays interacting with electronic process. The musical analysis is based on the relation between acoustical instrument and electronics and on the functions of each one in the Silvio Ferrazs poucas linhas de ana cristina. This work can be played with or without electronics and our interest is to know the musical functions of electronics. The analysis of poucas linhas de ana cristina has been done in three parts: (1) analysis of the clarinet score, (2) study of the functions of the electronic and (3) analysis of the relationship between clarinet and electronics. The first part was based exclusively on Silvio Ferrazs compositional thoughts related to Deleuze and Guattari texts. The study of the functions of the electronics focused the aspects of enlargement of instrumental resources. The last part took the clarinet score as a reference to an analysis based on Smalleys Spectromorphology concepts and some Ferrazs thoughts. We identified two types of behaviors from the electronics: (1) textural mass built behind the clarinet and (2) melodies in counterpoint with clarinet. There are two relationships between the clarinet and the electronics: (1) one of predominance and (2) one of equal relevancy. We believe that this type of analysis can help performers to play not only poucas linhas de ana cristina, but also other pieces of music that demand interaction of acoustic instruments and live electronics.